A comunidade ribeirinha do acampamento coragem e os defeitos da usina hidrelétrica de estreito (MA). - OLIVEIRA, Gerson da Silva (Universidade Federal do Tocantins, 2023)
The following work analyzes the residents‟ perception of the riverine community of Acampamento Coragem in Palmeiras do Tocantins (TO) municipality related to the effect provoked by the Estreito Hydroelectric Plant (UHEE), which is located in Maranhão State. It emphasizes the processes of deterritorialization and reterritorialization that the community is confronting since the installation of that plant, trying to evidence how the population has confronted those effects and the consequences occasioned to its ways of life. This study was made through qualitative inquiry, participant observation, field reports, and exploratory interviews. In that way, it is evidenced that after some years of the UEHH construction, the community still suffers the effects provoked as well as the conflicts by the land, the alteration of its riverine daily life and the drastic effects in the fish production that attain its cultural activities. Thereby, the struggle by the land and territory, resistance to occupying a riverine place, and the revindication of the camped population point out some affectivity trajectories with the place that exceeds the geographic sense of the occupation. This evidences the histories of life that rememorate the flooded territory.